Faktor Pendukung Berupa Fasilitas Sekolah Dalam Meningkatkan Kemampuan Numerasi Siswa - Rosi Aurora Nur Haliza; Afib Rulyansah; Nafiah Nafiah; Sri Hartatik (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
The purpose of this study is to describe the supporting factors in the form of facilities in improving the numeracy skills of students at SDN Margorejo 1 Surabaya. The method used is a descriptive qualitative approach with the main subjects in this study including the principal and homeroom teacher. The first data collection technique is direct observation, interviews, and documentation. Based on the results of research obtained from observations and interviews with resource persons, it can be concluded that there are several efforts that have been made by school principals in increasing numeracy skills that are in accordance with the contents of the discussion contained in the supporting material for numeracy literacy, which is to improve numeracy by doing habituation by giving story questions related to everyday life and starting from the simplest things by utilizing the environment around the school as a supporting facility. In line with previous research, there are several factors that students lack understanding about numeracy, including lack of habituation in giving story questions related to daily life, and training for teachers is needed to improve their teaching abilities.